Analysis of serum concentrations of metoprolol and its metabolite α-hydroxymetoprolol in patients with heart failure with reduced ejection fraction: a pilot study in routine health care - Kacirova, Ivana; Lazarova, Marie; Urinovska, Romana; Dodulik, Jozef; Vaclavik, Jan (Expert review of clinical pharmacology, 2025)
BACKGROUND: The cardioselective β-1 receptor antagonist metoprolol is used to treat heart failure. It is metabolized in the liver, primarily by cytochrome 2D6. RESEARCH DESIGN AND METHODS: In this study, trough serum concentrations of metoprolol and its metabolite α-hydroxymetoprolol were measured in patients with heart failure with reduced ejection fraction. RESULTS: Concentrations were 1.3-122.9 µg/L for metoprolol and 1.3-125.7 µg/L for α-hydroxymetoprolol, metabolic ratios were 0.11-98.32. The median weight-adjusted apparent clearance of metoprolol was 53.07 (range 3.24-500.0). Metoprolol and α-hydroxymetoprolol concentrations correlated with both daily dose and dose per kilogram of body weight. However, metoprolol concentrations at the same daily dose showed a wide variability. Patients taking 100 mg/day had significantly lower NT-proBNP values than those taking 25 or 50 mg/day. Patients with LVEF ≤ 35% versus > 35% used significantly lower daily doses and doses per kilogram of body weight, although metoprolol concentrations did not differ. A poor cytochrome 2D6 metabolizer phenotype was detected in two patients. CONCLUSIONS: Metoprolol concentrations showed a wide interindividual variability at the same daily dose. Simultaneous determination of metoprolol and α-hydroxymetoprolol concentrations could identify patients at risk of possible accumulation of metoprolol leading to intoxication or, conversely, patients at risk of underdosing. [Figure: see text].
Keywords: natriuretický peptid typu B; metoprolol; peptidové fragmenty; Metoprolol; Pilot Projects; Adrenergic beta-1 Receptor Antagonists; variability; Cytochrome P-450 CYP2D6; Body Weight; pilotní projekty; lidé středního věku; cytochrom P-450 CYP2D6; Dose-Response Relationship, Drug; ženské pohlaví; lidé; vztah mezi dávkou a účinkem léčiva; tepový objem; mužské pohlaví; senioři; srdeční selhání; Aged, 80 and over; Aged; senioři nad 80 let; Humans; concentrations; Heart Failure; Peptide Fragments; heart failure; tělesná hmotnost; Female; antagonisté beta-1-adrenergních receptorů; Middle Aged; Natriuretic Peptide, Brain; Male; α-hydroxymetoprolol; Stroke Volume